Study of the Transformation of Ecuador's Productive Structure, Technology, and GDP in Recent Years Using the IADOV Plithogenic Method - Pedro Gustavo Correa Mendoza; Pedro Gustavo Correa Mendoza; Shakila Devi G T; Darvin Manuel Ramírez Guerra (Neutrosophic Sets and Systems)
This study investigates the transformation of Ecuador's productive structure, technological integration, and its impact on GDP over the last decade, using the novel Plithogenic IADOV method. This approach, based on neutrosophic logic, allows for the analysis of complex economic scenarios characterized by indeterminacy and contradiction, aspects often overlooked by traditional methods. Through questionnaires administered to 40 experts, the research evaluates five key dimensions: economic diversification, technological integration, GDP growth, public policy formulation, and economic resilience. Findings reveal progress in diversification and technological integration, albeit limited, with a persistent strong reliance on primary sectors and technological gaps, especially for SMEs. While there is political intent to foster transformation, its application and effectiveness are questioned, with an unequal distribution of GDP growth benefits observed. The study concludes by proposing feasible improvements such as fostering emerging sectors, SME digitalization, and the creation of macroeconomic stabilization funds.